Catalytic wet air oxidation of olive mill wastewater - Gomes, Helder (2008)
The objective of this work was to study the suitability of catalytic wet air oxidation (CWAO) for the treatment of olive mill wastewater (OMW). Experiments were performed in a high pressure reactor at 100 and 200ºC under an oxygen partial pressure of 6.9 bar, using carbon supported platinum (1 wt.% Pt) and iridium (5 wt.% Ir) catalysts prepared by incipient wetness impregnation. At 100ºC, refractory organic compounds persisted even after prolonged reaction time (8 h). At 200ºC, complete total organic carbon and colour removal was obtained with the Pt/C catalyst after 8 h of reaction. A kinetic model was developed taking into account catalytic and non-catalytic reactions, formation of refractory compounds and catalyst deactivation. Very good agreement between the proposed model and CWAO experimental data at 200ºC was found. The results obtained in this work indicate that Pt/C is a promising catalyst for the CWAO of OMW.